2017
DOI: 10.18769/ijasos.309675
|View full text |Cite
|
Sign up to set email alerts
|

Pause and Slip of the Tongue on Stand Up Comedy Show in Indonesia

Abstract: Language and mind are connecting each other with mental process to decide ideas to what will be delivered in spoken language. Some contexts, including spoken humour, does not seldom occur errors in delivering. This case occurs to comica in creating humorous ideas delivering in stand-up comedy. This purpose of this research is to describe the pause and slip of the tongue that happens on stand-up comedy show in Indonesia. The research is the study psycholinguistics. Language and mind related to mental processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The finding in this study obtains the pattern of slips of the tongue in political discourse that involves pauses because of respiratory and hesitation, repetition and some speech errors that happened in the phonetic, syllables, and word. It is also similar to those produced by non-native speakers (Asyura, 2017) and involving more on the phonological segment (Frisch and Wright, 2002). Such slips happen as deviations in speech errors in the planning processes specifying the targets of articulation and articulatory processes specifying the motor movements that execute the utterance plan (Goldrik et al, 2016).…”
Section: Discussionsupporting
confidence: 63%
“…The finding in this study obtains the pattern of slips of the tongue in political discourse that involves pauses because of respiratory and hesitation, repetition and some speech errors that happened in the phonetic, syllables, and word. It is also similar to those produced by non-native speakers (Asyura, 2017) and involving more on the phonological segment (Frisch and Wright, 2002). Such slips happen as deviations in speech errors in the planning processes specifying the targets of articulation and articulatory processes specifying the motor movements that execute the utterance plan (Goldrik et al, 2016).…”
Section: Discussionsupporting
confidence: 63%
“…Nevertheless, the Rimawati research finding is still relevant where deletion and addition are the following dominant types after substitution just like what is found in this study. Whereas, the extreme different finding of the dominant type of slip is showed in another previous study conducted by the Asyura (2017) who found that anticipation is the most dominant type made by Indonesian Comica. The writer assumes that the language used by the sample also influenced the appearance of the dominant type of slip.…”
Section: Discussionmentioning
confidence: 74%
“…The factor is language education itself and also the age of the person. Older people tend to produce more tongue slips than younger ones, educated people can also minimize the production of slips of the tongue Asyura (2017) found that a female speaker also made fewer speech errors than a man. This research examines the stand-up comedians at one TV station in Indonesia.…”
Section: Factors Causing the Slips Of Tongue Of Male And Female Debatersmentioning
confidence: 97%
“…This research examines the stand-up comedians at one TV station in Indonesia. In practice, One of the female comedians did produce the least speech errors, but Asyura (2017) considered that the comedian's readiness factor was more influential in how much they produced speech errors. The comedian who prepare the material well, are not nervous, and are less confident in producing speech errors.…”
Section: Factors Causing the Slips Of Tongue Of Male And Female Debatersmentioning
confidence: 99%
See 1 more Smart Citation